Case Report: Severe Pneumocystis jirovecii pneumonia following zuberitamab treatment in autoimmune hemolytic anemia - Yang, Qian; Ding, Peng; Liu, Yu-xiang; Zhang, Kai-chen; Gao, Pei-yang (Frontiers in Immunology, 2025)
The pathogenesis of autoimmune hemolytic anemia (AIHA) remains incompletely understood, typically associated with immune dysfunction and the production of autoantibodies. Zuberitamab, a novel anti-CD20 monoclonal antibody, represents an important therapeutic strategy for managing autoimmune diseases. Here, we present the first case of a patient diagnosed with AIHA who developed severe immunosuppression, lymphopenia, and B-cell depletion following zuberitamab treatment, ultimately resulting in severe Pneumocystis jirovecii pneumonia(PJP). This case highlights the complexities of B-cell-targeted immunotherapy and underscores the necessity of close monitoring of immune status in patients receiving zuberitamab or other targeted immunotherapies to mitigate the risk of severe immune-related adverse events.